Ultrawideband Terahertz Absorber with Dielectric Cylinders Loaded Patterned Graphene Structure - Shuxiang Liu (MDPI AG, 2021)
In this paper, we theoretically designed and numerically analyzed an ultrabroadband meta-absorber with near unity absorptivity that works in terahertz spectrum. A wideband meta-absorber composed of bilayer patterned graphene and dielectric cylinder array with high symmetry was proposed. The wideband absorption mechanism benefited from two aspects. The first one was enhanced surface plasmons based on bilayer patterned graphene. And the second one was the coupling of continuous resonant modes within Fabry-Perot cavities to the enhanced surface plasmons in the graphene. An ultrawide bandwidth with absorptivity over <semantics>90%</semantics> were obtained from <semantics>3.2</semantics> THz to <semantics>9.4</semantics> THz. Simulated results showed that the proposed ultra-wideband absorbing structure also possessed high performance of polarization independence, flexible tunability, large incident angle insensitivity, and compact fabrication.